1997
DOI: 10.1080/096392897331451
|View full text |Cite
|
Sign up to set email alerts
|

Video simulation of an audit: an experiment in experiential learning theory

Abstract: This paper reports the results of a controlled eld experiment carried out to apply experiential learning theory to the teaching of auditing. The weakest aspect of traditional teaching method is the absence of concrete experience. In this experiment, a series of videotapes provide students with a 'feel' for what actually happens in an audit. The experiment involves the rst three modes of the learning cycle, and assists students into the fourth mode. The performance of students in the experimental class is found… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
13
0

Year Published

2002
2002
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(17 citation statements)
references
References 19 publications
4
13
0
Order By: Relevance
“…□ insight into the practical operations of an audit (84%) -this finding is similar, inter alia, to those of Arens et al (1970), Siegel et al (1997) and Massey et al (2002); □ the skills to interpret large volumes of data (defined as the ability to understand and decipher data) (83%); □ the skill to relate theory and technical knowledge in Auditing to real-life situations or practical problems (with complexities and ambiguous information) (81%); □ the ability to summarise data (74%); □ the ability to integrate the understanding of the different components of Auditing courses (73%); and □ the encouragement of students to apply their theoretical knowledge to new and unique situations (71%). The results for these 29 questions indicated that the main objectives of the simulation, namely to integrate Auditing with IT and to make Auditing more practical, had been achieved.…”
Section: Usefulness Of the Audit Simulation For Teaching Various Compsupporting
confidence: 87%
See 1 more Smart Citation
“…□ insight into the practical operations of an audit (84%) -this finding is similar, inter alia, to those of Arens et al (1970), Siegel et al (1997) and Massey et al (2002); □ the skills to interpret large volumes of data (defined as the ability to understand and decipher data) (83%); □ the skill to relate theory and technical knowledge in Auditing to real-life situations or practical problems (with complexities and ambiguous information) (81%); □ the ability to summarise data (74%); □ the ability to integrate the understanding of the different components of Auditing courses (73%); and □ the encouragement of students to apply their theoretical knowledge to new and unique situations (71%). The results for these 29 questions indicated that the main objectives of the simulation, namely to integrate Auditing with IT and to make Auditing more practical, had been achieved.…”
Section: Usefulness Of the Audit Simulation For Teaching Various Compsupporting
confidence: 87%
“…This finding is similar to that of the other studies in this section. Siegel et al (1997) reported on a video simulation of an audit, The CableCo Chronicles. The set of four videos, supported by written materials, takes the students through the audit process -from acquiring a new audit client to the concluding stages of the audit.…”
Section: Literature Reviewmentioning
confidence: 99%
“…As the lack of a practical element in university audit teaching has been an issue raised in the literature (Siegel et al, 1997), the questionnaire asked audit lecturers and students about how useful they thought practical experience, ranging from guest lectures to case studies to a period of work experience, would be to aid students' understanding of auditing. Table 6 shows that case studies were seen to be an important feature of audit classes, especially in tutorials, but that they featured also for use by groups outside the classroom.…”
Section: Experiential Learningmentioning
confidence: 99%
“…An effort was made to select questions that were not biased toward the teaching methods using a conceptual model. Both Mohrweis (1993) and Siegel et al (1997) use objective questions to assess student learning, but neither separately assesses the questions by the type of student learning that is being assessed. 4 A limitation to this approach is that these types of questions may not capture the potentially greater richness that more active learning environments offer.…”
Section: As S E S S M E Nt I Ns T R Um E Ntmentioning
confidence: 99%